A systematic review of menopause apps with an emphasis on osteoporosis - Deborah Paripoorani; Norina Gasteiger; Helen Hawley-Hague; Dawn Dowding (BMC, 2023)
Abstract Background Menopause can significantly hasten bone loss. Mobile phones provide an efficient way to manage, track and understand menopause using apps. A previous review of menopause apps found numerous apps designed to help women manage menopause. However, it did not use validated measures to assess the quality of the apps and did not focus on content related to osteoporosis. Methods This app review aligns with the updated Preferred Reporting Items for Systematic Reviews and Meta-Analysis guidelines. The keywords used to search for the apps were "menopause" and "menopausal". Apps were included if they were in English, for individuals or groups and had a lifestyle focus. Apps that looked at other aspects of women's health, required external devices, cost to download, or were symptom-tracking were excluded. The quality and functionality were assessed using the Mobile App Rating Scale and IMS Institute for Healthcare Informatics Functionality score. Data were synthesised descriptively. Results Twenty-eight apps were selected and reviewed from the 236 apps screened from the Apple store and Google play store. Only 57% of the apps reviewed (n = 16) had content on osteoporosis which was educational in purpose. The readability of the apps was complex and best understood by university graduates. The average functionality score of the apps reviewed was 4.57 out of 11 and that of quality is 3.1 out of 5, both of which need improvement. Conclusions Existing menopause apps need more input from experts to improve the quality and functionality, using simple language. More emphasis on specific health problems during menopause, including osteoporosis, is required. Trial registration Not relevant.